Governing without Governed and Governors: An Attempt to Establish a Non-Hierarchical Organizational Repertoire - Lukáš Kotyk (Partecipazione e Conflitto, 2020)
This study focuses on attempts to establish non-hierarchical structures and decision-making processes within a squatters' movement, where these modes of self-organizing are usual. Beneath the declaration of a non-hierarchical structure, many variations and perspectives on how to achieve such a goal may be concealed. Besides formal meetings of the collective where common decisions are made, a horizontal logic of sharing space as a commons has to be maintained in everyday life. A reflexive attitude toward the distribution of power is a key aspect of managing the tension that arises between the idealized vision of horizontality and the efforts that are made to realize it. I analyse how the experiment with non-hierarchical organization is carried out in a squatted garden in a city in southern France, where people live in huts and trailers and share a legally rented common house on a connected parcel of land. By using ethnography, in which semi-structured interviews and participant observation form a crucial part, I interpret the inner dynamics of a concrete collective and its strategies to maintain a non-hierarchical logic. I focus on the tools, methods and practices that are used by the participants to keep the distribution of power horizontal and on their reflection on this process. Studying a case such as this will shed light on the variations in how a sustainable project on squatted land can be formed. Analysing one possibility that appears to be successful, and its interpretation within the context of new left movements, help us to better understand prefigurative attempts at creating alternative forms of coexistence.